The Extent of Benefiting from Artificial Intelligence Technique in Creating Designs Inspired by Al-Asiri Cat Ornaments to Enrich Clothing Accessories - Abdelaziz, Walaa Mohamed (Journal of Humanities & Social Sciences, 2025)
The current study aimed to recognize the capabilities of A.I technology and take advantage of its applications to reach contemporary decorative formulaic building designs to enrich garment supplements and develop designs inspired by Alqatt al asiri decorations to reach aesthetic values and innovative formulas for Alqatt al asiri through A.I technology. To achieve the objectives of the study, the researcher followed the analytical descriptive curriculum of a sample of (5) designs of women's clothing supplements (Shoe, Women's Bag, Accessories, Hat and Belt) is designed using AI technology in terms of the potential of AI technology and decorative shape construction of garment supplements, the development of contemporary decorative designs as well as aesthetic values of compact ornaments and to answer study questions. The researcher prepared the study tools represented in the content analysis tool and used the SPSS programme to analyse data. The results have found that AI technology has helped to develop decorative design methods and reproduce decorations in innovative ways for garment supplements. It has also contributed to the advancement of diverse solutions for the designer in the creation of digital designs and in record time, as well as affirming the concept of authenticity and heritage by drawing inspiration for the Alqatt al asiri decorations and using them in a modern manner. In the light of previous findings, the researcher recommends that AI techniques should be used to design contemporary products for clothing supplements and develop decorative design methods to enable designers to create clothing supplements inspired by Alqatt al asiri.
Keywords: Artificial Intelligence Technology; Design; Alqatt al asiri Decorations; Clothing Supplements